Temporal and spatial deviation in F2 peak parameters derived from FORMOSAT-3/COSMIC - Kumar, Sanjay; Singh, R.P.; Tan, Eng Leong; Singh, A.K.; Ghodpage, R.N.; Siingh, Devendraa (My University, 2016)
The plasma frequency profiles derived from the Constellation of Observing System for Meteorology, Ionosphere and Climate (COSMIC) radio occultation measurements are compared with ground-based ionosonde data during the year 2013. Equatorial and midlatitude five stations located in the Northern and Southern Hemisphere are considered: Jicamarca, Jeju, Darwin, Learmonth, and Juliusruh. The aim is to validate the COSMIC-derived data with ground-based measurements and to estimate the difference in plasma frequency (which represents electron density) and height of F2 layer peak during the daytime/nighttime and during different seasons by comparing the two data sets. Analysis showed that the nighttime data are better correlated than the daytime, and the maximum difference occurs at the equatorial ionospheric anomaly (EIA) station as compared to lower and midlatitude stations during the equinox months. The difference between daytime and nighttime correlations becomes insignificant at midlatitude stations. The statistical analysis of computed errors in foF2 (hmF2) showed Gaussian nature with the most probable error range of ±15% (±10%) at the equatorial and EIA stations, ±9% (±7%) outside the EIA region which reduced to ±8% (±6%) at midlatitude stations. The reduction in error at midlatitudes is attributed to the decrease in latitudinal electron density gradients. Comparing the analyzed data during the three geomagnetic storms and quiet days of the same months, it is observed that the differences are significantly enhanced during storm periods and the magnitude of difference in foF2 increases with the intensity of geomagnetic storm.
Keywords: Plasmas; Ground based Ionosonde data; COSMIC; FORMOSAT